Strategies to Reduce Biofilm Formation in PEEK Materials Applied to Implant Dentistry-A Comprehensive Review - Renata Scheeren Brum; Luiza Gomes Labes; Cláudia Ângela Maziero Volpato; César Augusto Magalhães Benfatti; Andrea de Lima Pimenta (MDPI AG, 2020)
Polyether-ether-ketone (PEEK) has emerged in Implant Dentistry with a series of short-time applications and as a promising material to substitute definitive dental implants. Several strategies have been investigated to diminish biofilm formation on the PEEK surface aiming to decrease the possibility of related infections. Therefore, a comprehensive review was carried out in order to compare PEEK with materials widely used nowadays in Implant Dentistry, such as titanium and zirconia, placing emphasis on studies investigating its ability to grant or prevent biofilm formation. Most studies failed to reveal significant antimicrobial activity in pure PEEK, while several studies described new strategies to reduce biofilm formation and bacterial colonization on this material. Those include the PEEK sulfonation process, incorporation of therapeutic and bioactive agents in PEEK matrix or on PEEK surface, PEEK coatings and incorporation of reinforcement agents, in order to produce nanocomposites or blends. The two most analyzed surface properties were contact angle and roughness, while the most studied bacteria were Escherichia coli and Staphylococcus aureus. Despite PEEK's susceptibility to biofilm formation, a great number of strategies discussed in this study were able to improve its antibiofilm and antimicrobial properties.